2012
DOI: 10.1155/2012/371286
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma tsugaeInduces S Phase Arrest and Apoptosis in Doxorubicin-Resistant Lung Adenocarcinoma H23/0.3 Cells via Modulation of the PI3K/Akt Signaling Pathway

Abstract: Ganoderma tsugae (GT) is a traditional Chinese medicine that exhibits significant antitumor activities against many types of cancer. This study investigated the molecular mechanism by which GT suppresses the growth of doxorubicin-resistant lung adenocarcinoma H23/0.3 cells. Our results reveal that GT inhibits the viability of H23/0.3 cells in vitro and in vivo and sensitizes the growth suppression effect of doxorubicin on H23/0.3 cells. The data also show that GT induces S phase arrest by interfering with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…The protein levels of cyclin E and CDK2 were modulated by the downregulation of AKT1, whereas the protein levels of Rb were slightly decreased (Figure 4c). Some studies have shown that the inhibition of p-AKT and AKT promotes the downregulation of cyclin E. 41 The downregulation of cell cycle regulatory proteins, such as Rb, cyclin E, and CDK2, induces an S-phase cell cycle arrest. 42 Actually, the miR-9500-transfected A549 cells had an increased number of cells in the G1 phase, as well as a reduced number of S and G2/M phase cells, according to flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The protein levels of cyclin E and CDK2 were modulated by the downregulation of AKT1, whereas the protein levels of Rb were slightly decreased (Figure 4c). Some studies have shown that the inhibition of p-AKT and AKT promotes the downregulation of cyclin E. 41 The downregulation of cell cycle regulatory proteins, such as Rb, cyclin E, and CDK2, induces an S-phase cell cycle arrest. 42 Actually, the miR-9500-transfected A549 cells had an increased number of cells in the G1 phase, as well as a reduced number of S and G2/M phase cells, according to flow cytometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the anticancer agents, a number of TCMs and botanical products have been shown to be effective and useful adjuvant agents for the treatment of HER2-overexpressing cancer [5, 6, 26]. Ganoderma tsugae (GT), one of the most common species of Ganoderma cultivated in Taiwan, has been shown to have antiproliferative effects on human cancer cells [15, 16, 18]. In this study, we report for the first time that the extract of GT (GTE) has a distinct growth-inhibitory effect on HER2-overexpressing cancer cells in vitro (Figures 1(a)–1(c)) and in vivo (Figure 5(a)).…”
Section: Discussionmentioning
confidence: 99%
“…A number of TCMs (e.g., GT) exhibit marked growth-inhibitory effects on cancer cells via disruption of cell cycle progression. Previous reports show that GT inhibits cell proliferation by inducing cell cycle arrest in the G2/M phase in Hep3B hepatoma and COLO205 colorectal cancer cells [15, 17] and in the S phase in H23/0.3 lung adenocarcinoma cells [18]. In this study, our in vitro results indicate that GTE treatment induces G1 phase arrest via modulation of cell cycle regulators (e.g., cyclins D1 and E, p21, and p27) in HER2-overexpressing SKOV-3 ovarian cancer and BT-474 breast cancer cells (Figure 2 and Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations